0
$\begingroup$

Good day

I am getting confused on Boolean function simplification. I dont quite understand how the equation is simplified as in the rules for simplification in boolean algebra.

Can anyone help explain how i would simplify these two examples.

AB'C + (AB'C)D'

x + (x + xy) + y(xy')'

Thank you

$\endgroup$
0
$\begingroup$

Here is a good reference http://www.electronics-tutorials.ws/boolean/bool_6.html So the first expression can be simplified to AB'C (if it's value is true, the whole expression is true, if it's false, the whole expression is false, D does not matter). The second expression can be reduced to x + y, I think (x+xy=x, x+x=x, etc).

$\endgroup$
0
$\begingroup$

Here are some basic simplification rules:

Double Negation

$P''=P$

DeMorgan

$(PQ)' = P' + Q'$

$(P + Q)' = P'Q'$

Absorption

$P + PQ = P$

$P(P+Q)=p$

Idempotence

$P+P=P$

$PP = P$

With these, you can 'solve' both of your problems.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.